1999
DOI: 10.1046/j.1365-3024.1999.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity in the rat model of congenital toxoplasmosis and the potential of excreted‐secreted antigens as vaccine components

Abstract: Toxoplasma infection is a major cause of severe foetal pathology both in humans and in domestic animals, particularly sheep. We have previously reported the development of an experimental model to study congenital toxoplasmosis in the rat. Here we demonstrate that, as in humans, total protection against congenital toxoplasmosis can be achieved regardless of the strain of Toxoplasma gondii used to infect rats, or when initial and challenge infections were carried out with different strains. Chronic infection is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…Costa-Silva et al (2008) reported that ESA immunized mice had lower parasitaemia as well as longer survival then mice in the control group. Zenner et al (1999) have reported that purified ESA, namely GRA2 and GRA5, had a significant degree of organs' protection. Furthermore, a study conducted by Daryani et al (2003) showed that the ESA-F2 antigens could be used as a good candidate for the development of new immunization strategy against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Costa-Silva et al (2008) reported that ESA immunized mice had lower parasitaemia as well as longer survival then mice in the control group. Zenner et al (1999) have reported that purified ESA, namely GRA2 and GRA5, had a significant degree of organs' protection. Furthermore, a study conducted by Daryani et al (2003) showed that the ESA-F2 antigens could be used as a good candidate for the development of new immunization strategy against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this model is the high susceptibility of certain strains of mice to toxoplasmosis, with a high rate of mortality during acute infection. Interestingly, in respect to clinical course and in utero transmission, toxoplasmoses in rats and humans are similar, and the infection in rats can serve as a model for human toxoplasmosis (6,26,(33)(34)(35). Hence, like humans, rats do not succumb to acute toxoplasmosis even with a high inoculum of Toxoplasma strains that are highly virulent in mice.…”
mentioning
confidence: 99%
“…The highest protection against congenital disease, however, was obtained in a rat model (Zenner et al 1999). However, in these models, the correlates of protection have not been elucidated.…”
Section: Discussionmentioning
confidence: 98%